It's all in the stars: The Chinese zodiac and the effects of parental investments on offspring's cognitive and noncognitive skill development - Tan, Chih Ming; Wang, Xiao; Zhang, Xiaobo (Wiley, 2024)
Parental investments in children's cognitive and noncognitive outcomes are deeply important to policymakers. However, because parental investments are arguably endogenous, estimating their importance empirically poses a challenge. To address this challenge, this paper exploits a rich and novel dataset, the China Family Panel Studies, and proposes a culture‐specific instrumental variable based on the Chinese zodiac. By comparing the outcomes of children born just before and just after the cutoff for a “lucky” (or ‘unlucky’) zodiac sign, we find that parents' investments have significant effects on offspring's development of both cognitive and noncognitive skills.